2012
DOI: 10.1111/aae.12000
|View full text |Cite
|
Sign up to set email alerts
|

Crossing the Indian Ocean before the Periplus: a comparison of pottery assemblages at the sites of Sumhuram (Oman) and Tissamaharama (Sri Lanka)

Abstract: There is a long tradition of studies of the Indian Ocean trade focused almost exclusively on the trade between Roman Egypt and India. Less attention has been paid to the formative period of early historical long-distance trade in the Indian Ocean. The aim of this paper is to discuss some aspects of the development of this trade, based on an analysis of the South Asian pottery found at two different settlements: Sumhuram in the Sultanate of Oman and Tissamaharama in Sri Lanka.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…2006) and, within the Roman world, from the port sites of Berenike and Myos Hormos on the northern Red Sea in Egypt (Tomber 2000: 630, 2002: 27, 2008). Coarse dishes with beaked rims are also known from Sumhuram in Oman (Pavan & Schenk 2012).…”
Section: Multiple Early Contacts With India and Mainland Southeast Asiamentioning
confidence: 99%
See 1 more Smart Citation
“…2006) and, within the Roman world, from the port sites of Berenike and Myos Hormos on the northern Red Sea in Egypt (Tomber 2000: 630, 2002: 27, 2008). Coarse dishes with beaked rims are also known from Sumhuram in Oman (Pavan & Schenk 2012).…”
Section: Multiple Early Contacts With India and Mainland Southeast Asiamentioning
confidence: 99%
“…In South Asia, coarse dishes in the shape of Rouletted Ware were not found in northern India, but were widely found in Sri Lanka and southern India, together with Rouletted Ware. The second century BC south Indian and Sri Lankan production of coarse-fabric dishes imitating the shape of Rouletted Ware, which instead was imported from the Ganges Valley of northern India, has been argued for based on the pottery sequence at Tissamaharama in Sri Lanka (Schenk 2001, 2006; Pavan & Schenk 2012). A single geological origin for fine grey-fabric Indian ware, including Rouletted Ware and Northern Black Polished Ware, is indicated by geochemical data (Ardika et al .…”
Section: Multiple Early Contacts With India and Mainland Southeast Asiamentioning
confidence: 99%
“…Even if the significance of the Mediterranean connection has been played down over time, Arikamedu has retained its position in the study of Indian Ocean trade. Beads as well as pottery associated with the site have become highly useful proxies for tracing trading connections, emphasizing the centrality of South India and Sri Lanka in connecting the Arabian Sea and Bay of Bengal circuits of trade (Gupta 2005;Pavan and Schenk 2012). The new studies and excavations at Arikamedu clearly show a site with a much wider significance in terms of chronology and commercial as well as cultural diversity than the "Roman factory" inferred by Wheeler, but they have not yet revealed much about the socioeconomic organization of the ancient port (Tomber 2008, pp.…”
Section: South Asiamentioning
confidence: 99%
“…References in literary sources (Weerakkody 1997) and large finds of late Roman bronze and copper coins, also found in South India and apparently imported in bulk (Bopearachchi 1992(Bopearachchi , 1998, long gave the impression that the island did not emerge as an important node in commerce with the Persian Gulf and the Red Sea until the fourth to sixth centuries AD. Excavations at Tissamaharama, along with studies of ceramics from Mantai and Anuradhapura (Carswell 1991;Carswell et al 2013;Coningham 2002Coningham , 2006Coningham et al 1996;Coningham and Raymond 1999;Ford et al 2005;Pavan and Schenk 2012;Schenk 2001Schenk , 2006Schenk , 2007, however, have demonstrated that the island's nodal role can be traced back at least to the third century BC. The ship cargo of the second to first centuries AD that was discovered in 2008 off the ancient port of Godavaya in southern Sri Lanka is still under excavation, but preliminary publications and news reports have announced finds of glass ingots and metal, possibly of Indian provenance (Carlson 2010;Lawler 2012).…”
Section: South Asiamentioning
confidence: 99%
“…As of yet, no finds have been made in the region, for instance, of imported cooking pots that have been interpreted as a proxy of resident foreign communities at Red Sea and Indian Ocean ports such as Berenike, Myos Hormos, and Khor Rori (Pavan and Schenk 2012;Tomber 2012). Nevertheless, there is good literary evidence of diaspora settlements in the region, including, besides Rufinus' account, a reference in the first-century Periplus of the Erythraean Sea to the import of coinage for the resident foreign merchants (Casson 1989, pp.…”
Section: Trade Social Network and The Introduction Of Christianitymentioning
confidence: 99%